1989
DOI: 10.1002/mus.880120408
|View full text |Cite
|
Sign up to set email alerts
|

The application of nerve conduction and clinical studies to genetic counseling in hereditary motor and sensory neuropathy type I

Abstract: One hundred and thirty two individuals at risk for hereditary motor and sensory neuropathy (HMSN) type I from 11 unrelated families were evaluated by physical examination. Motor conduction velocity (MCV) studies of median and/or peroneal nerves were performed on 99 of them. Seventy-three subjects were found to be affected. In all age categories including the first decade of life, the ratio of affected individuals at risk did not significantly differ from the expected 1:1 ratio; that is, penetrance of the gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…Contrariwise, pes cavus is just mentioned in 20 out of 62 (32%) so far reported CMT2J patients [15,29,41,43], though in one series all 16 patients showed either pes cavus (11 cases) or pes planus (5 cases) [29]. Adult symptomatic onset in CMT2J, after completion of bony development, most probably accounts for the low range of pes cavus in comparison with any other early onset CMT1 or CMT2 syndromes [3,6,10,48]. In our pedigree both the proband and her affected son, with symptomatic onset at 40 and 27 years, showed marked and unnoticed forefoot pes cavus and massive wasting of intrinsic foot musculature, a fact suggesting that the process of distal axonopathy in lower leg nerves was initiated much earlier to the stated age of symptomatic onset.…”
Section: Discussionmentioning
confidence: 91%
“…Contrariwise, pes cavus is just mentioned in 20 out of 62 (32%) so far reported CMT2J patients [15,29,41,43], though in one series all 16 patients showed either pes cavus (11 cases) or pes planus (5 cases) [29]. Adult symptomatic onset in CMT2J, after completion of bony development, most probably accounts for the low range of pes cavus in comparison with any other early onset CMT1 or CMT2 syndromes [3,6,10,48]. In our pedigree both the proband and her affected son, with symptomatic onset at 40 and 27 years, showed marked and unnoticed forefoot pes cavus and massive wasting of intrinsic foot musculature, a fact suggesting that the process of distal axonopathy in lower leg nerves was initiated much earlier to the stated age of symptomatic onset.…”
Section: Discussionmentioning
confidence: 91%
“…In one series of 18 patients with CMT1A, weakness was not seen before the age of 10 years, but it was apparent in 50% of those age 10 -20 years. 6 In another small series, weakness was not evident before the age of 5 years, but it was seen in 10% of children age 5-10 years and 70% of those age 11-19 years. 22 We found that foot and ankle strength in children with CMT1A is abnormal from an early age.…”
Section: Discussionmentioning
confidence: 95%
“…This frequency is considerably lower than rates reported in previous studies: 33% of children under 5 years, 7 55% of children age 5-10 years, 22 and 87% of adolescents age 10 -20 years. 6 Differences in the prevalence of pes cavus may relate to the method by which it is evaluated. Most studies have simply looked for the presence or absence of pes cavus, while we quantified foot structure along a continuum of severity using the FPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has no predilection for a particular race or sex. Charcot-Marie-Tooth disease (CMT) is (7) among the most common inherited neurological disorders, with a prevalence reported (13,14) as high as 36 per 100 000 (Skre, 1974). The syndrome was initially described by Charcot and Marie in France (Charcot and Marie, 1886) and Tooth in England (Tooth, 1886) and confirmed (8,9) to be a disorder of the PNS by Hoffman (Hoffmann, 1889).…”
Section: Epidemiologymentioning
confidence: 99%